Предмет: Алгебра,
автор: AlinkaPik
упростите выражение -0,5x(2x-3)-(4x+3)(1-2x)
Ответы
Автор ответа:
0
-0.5х * 2х -0.5х* (-3) -4х*1 -4х*(-2х) -3*1-3*(-2х) =
-х² +1.5х - 4х +8х² - 3 + 6х=
7х² +3.5х - 3
-х² +1.5х - 4х +8х² - 3 + 6х=
7х² +3.5х - 3
Автор ответа:
0
-x^2 +1.5x-4x-3+8x^2 +6x = 7x^2 +3.5x -3
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: s862160040099128
Предмет: Русский язык,
автор: shahnuralimov
Предмет: Экономика,
автор: aidikbn
Предмет: Литература,
автор: Аноним